Public financing and institutional isomorphism in Civil Society Organizations in Yucatán, México (2019)
This paper analyzes the public funding at Federal and State level granted to Civil Society Organizations (CSOs) of Yucatan, Mexico during the period 2006-2017. Based on the neo-institutional approach and the concept of institutional isomorphism are addressed patterns of distribution in the allocation of resources, the characteristics of CSOs and the amounts reported that allow knowing interaction between CSOs with the State and Federal government. The descriptive empirical study answers the question of what is the government's behavior in the allocation of Federal and State public resources to CSOs in Yucatan? and it focuses on the analysis of the information provided by the Federal Register of CSOs, as well as requests for public information based on the Right to Access to Public Information in Mexico. Findings about four types of isomorphisms mentioned by literature are addressed: thematic, legal, political and professionalizing. Related to findings in amounts, first, the concentration of 40% of the total amount granted at the federal level by the Ministry of Education (SEP) to the Pro-Education Board of Adults of the State of Yucatan, an organization identified as a “Non-Governmental Government Organization”, second, the state government with 43% of the total amount reported in the period granted from the Ministry of Rural Development (SEDER), a unit focused on increasing the productivity of sectors such as agriculture, livestock, fishing and aquaculture. This research contributes to the discussion and knowledge about the behavior of public financing at the subnational level directed to CSOs - not explored in Mexico - under a theoretical framework relevant to the third sector.